2009
DOI: 10.1016/j.saa.2009.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and DFT studies of flurbiprofen as dimer and its Cu(II) and Hg(II) complexes

Abstract: The vibrational study in the solid state of flurbiprofen and its Cu(II) and Hg(II) complexes was performed by IR and Raman spectroscopy. The changes observed between the IR and Raman spectra of the ligand and of the complexes allowed us to establish the coordination mode of the metal in both complexes. The comparative vibrational analysis of the free ligand and its complexes gave evidence that flurbiprofen binds metal (II) through the carboxylate oxygen. The fully optimized equilibrium structure of flurbiprofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…The energy gap between HOMO and LUMO is a critical parameter in describing molecular electrical transport properties [28]. In recent times the energy gap between HOMO and LUMO were used to prove the bioactivity from intermolecular charge transfer [62][63]. In this present study, the 3D structure of the HOMO and LUMO for the title molecule are shown in Fig.…”
Section: Fig 5 Frontier Molecular Orbitals Of Sitagliptinmentioning
confidence: 84%
“…The energy gap between HOMO and LUMO is a critical parameter in describing molecular electrical transport properties [28]. In recent times the energy gap between HOMO and LUMO were used to prove the bioactivity from intermolecular charge transfer [62][63]. In this present study, the 3D structure of the HOMO and LUMO for the title molecule are shown in Fig.…”
Section: Fig 5 Frontier Molecular Orbitals Of Sitagliptinmentioning
confidence: 84%
“…Therefore, it is clear that the charge transfer (CT) occurs in serotonin. The energy gap between MOs has been confirmed to show the bioactivity based on the intramolecular charge transfer (ICT) [57,58].…”
Section: Homo-lumo Analysismentioning
confidence: 95%
“…10. HOMO-LUMO energy gap is used as a quantum chemical descriptor in establishing correlations for chemical and biochemical systems [33]. A large HOMO-LUMO gap implies high stability for the molecules in the sense of its lower charge transfer in complexes.…”
Section: Frontier Molecular Orbitalsmentioning
confidence: 99%